Effect of Quenching Media on Mechanical Properties of Medium Carbon Steel 1030 (Journal of University of Babylon for Engineering Sciences, 2018)
This investigation aims to study the effect of quenching media (water, oil, Poly Vinyl Chloride PVC) on mechanical properties of 1030 steel. The applications of this steel include machinery parts where strength and hardness are requisites. The steel is heated to about 950  and soaked for 1hr in electrical furnace and then quenched in different quenching medium such as water, oil and poly vinyl chloride. After heat treatment by quenching, the specimens are tempered at 250  for 1hr and then cooling in air. The mechanical properties of the specimens are determined by using universal tensile testing machine for tensile test, Vickers hardness apparatus for hardness testing, measuring the grain size of the phases and examine the microstructure of the specimens before and after heat-treatment.The results of this work showed that improving the mechanical properties of medium carbon 1030 steel, which is quenching by water gives the preferred results as the following: Quenching by water leads to increase σy, σu.t.s, K and hardness, but at the same time quenching by water leads to decrease E and n. Also the quenching by water and followed by tempering leads to improve the microstructure and decreasing (refining) of the grain size of ferrite and pearlite phases of the steel used in this work.